Filamentous fungal pellets as versatile platforms for cell immobilization: developments to date and future perspectives - Minami Ogawa; Jaime Moreno-García; Tyler J. Barzee (Microbial Cell Factories)
Abstract Filamentous fungi are well-known for their efficiency in producing valuable molecules of industrial significance, but applications of fungal biomass remain relatively less explored despite its abundant and diverse opportunities in biotechnology. One promising application of mycelial biomass is as a platform to immobilize different cell types such as animal, plant, and microbial cells. Filamentous fungal biomass with little to no treatment is a sustainable biomaterial which can also be food safe compared to other immobilization supports which may otherwise be synthetic or heavily processed. Because of these features, the fungal-cell combination can be tailored towards the targeted application and be applied in a variety of fields from bioremediation to biomedicine. Optimization efforts to improve cell loading on the mycelium has led to advancements both in the applied and basic sciences to understand the inter- and intra-kingdom interactions. This comprehensive review compiles for the first time the current state of the art of the immobilization of animal, yeast, microalgae, bacteria, and plant cells in filamentous fungal supports and presents outlook of applications in intensified fermentations, food and biofuel production, and wastewater treatment. Opportunities for further research and development were identified to include elucidation of the physical, chemical, and biological bases of the immobilization mechanisms and co-culture dynamics; expansion of the cell-fungus combinations investigated; exploration of previously unconsidered applications; and demonstration of scaled-up operations. It is concluded that the potential exists to leverage the unique qualities of filamentous fungus as a cellular support in the creation of novel materials and products in support of the circular bioeconomy.